Fermions Tunneling from Higher-Dimensional Reissner-Nordstrom Black Hole: Semiclassical and Beyond Semiclassical Approximation - Yang, ShuZheng; Wen, Dan [UNESP]; Lin, Kai (Hindawi Ltd, 2016)
Based on semiclassical tunneling method, we focus on charged fermions tunneling from higher-dimensional Reissner-Nordstrom black hole. We first simplify the Dirac equation by semiclassical approximation, and then a semiclassical Hamilton-Jacobi equation is obtained. Using the Hamilton-Jacobi equation, we study the Hawking temperature and fermions tunneling rate at the event horizon of the higher-dimensional Reissner-Nordstrom black hole space-time. Finally, the correct entropy is calculation by the method beyond semiclassical approximation.